The effect mechanism of perceived entrepreneurial environment on Chinese college students’ entrepreneurial intention: chain mediation model test - Lin, Qicheng; Chen, Yirong; Lai, Junli; Zhang, Xinyi (Frontiers in Psychology, 2024)
This study aimed to explore the effect of perceived entrepreneurial environment among Chinese college students' entrepreneurial intention and its underlying mechanism, based on a survey of 445 college students from 5 universities with the perceived entrepreneurial environment assessment scale, the achievement motivation scale, the entrepreneurial self-efficacy scale, and the entrepreneurial intention questionnaire. The data were collected through a survey questionnaire that was distributed to tertiary students. Based on the theory of the entrepreneurial intention model, descriptive analysis, person correlation analysis, hierarchical regression, and structural equation modeling were used to analyze the collected data. The results indicated that: There were significant correlations among perceived entrepreneurial environment, achievement motivation, entrepreneurial self-efficacy, and entrepreneurial intention, and perceived entrepreneurial environment could significantly positively predict entrepreneurial intention.Achievement motivation and entrepreneurial self-efficacy played significant mediating roles between the perceived entrepreneurial environment and entrepreneurial intention. There were three paths that perceived entrepreneurial environment to influence entrepreneurial intention: One was the mediating role of achievement motivation; The second was the mediating role of entrepreneurial self-efficacy; The third was the chain-mediated role of both achievement motivation and entrepreneurial self-efficacy. This study examine the relationship between Chinese college students' perceived entrepreneurial environment and their entrepreneurial intention, along with its underlying mechanisms, provides a theoretical basis for training and guiding the entrepreneurship of college students. But it remains unclear whether the findings can be generalized to other populations, and further research is needed to test the robustness of the conclusions.